Mapping of quantitative trait loci for early seed germination using whole-genome resequencing chromosome segment substitution lines of aus Kasalath in the background of japonica Nipponbare - Shan, Siyao; Ye, Muhan; Ruan, Jue; Teng, Sheng; Yu, Min (Frontiers in Plant Science, 2025)
Direct-seeding systems in rice require cultivars with enhanced seed vigor to ensure rapid and uniform germination. In this study, a population of 42 chromosome segment substitution lines (CSSLs) derived from aus Kasalath in the japonica Nipponbare background, coupled with whole-genome resequencing data, was analyzed to identify quantitative trait loci (QTLs) associated with early seed germination. Phenotypic traits, including germination percentage (GP), germination rate (GR), and germination index (GI), were measured over two consecutive years to ensure robustness. Six stable QTLs were identified, with qSV-1 on chromosome 1 (30.10–30.94 Mb) emerging as the most consistent across evaluations for GP and GI. Functional annotation and gene expression analyses of the 840-kb qSV-1 interval pinpointed C3H10 and OsOFP3 as the primary candidate genes for further investigation. This study underscores the effectiveness of whole-genome resequencing paired with the CSSL platform for precise QTL identification, thereby providing critical genetic resources for improving seed vigor through marker-assisted breeding and functional genomics.